TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM PEMBUATAN AKTA JUAL BELI (AJB) YANG CACAT HUKUM DIKAITKAN PEMBERIAN SANKSI DALAM PELAKSANAAN JABATAN - Pratiwi, Novita; Anriz Nazaruddin Halim; Yuliana Setiadi (Bajang Institute, 2025)
The deed of sale and purchase (AJB) which is legally flawed due to PPAT negligence creates legal uncertainty (dassein), whereas the deed of sale and purchase (AJB) should guarantee legal protection and certainty over land rights (dassollen). This requires the enforcement of responsibility and the imposition of sanctions to maintain the integrity of the land system. This study raises two problems, namely (1) how the responsibility of the land deed officer (PPAT) to the deed of sale and purchase (AJB) containing legal defects associated with sanctions in the exercise of office and (2) how the legal certainty of the deed of sale and purchase (AJB) made by the land deed officer (PPAT) containing legal defects, using the theory of legal responsibility according to Hans Kelsen and The Theory of legal certainty according to Satjipto Rahardjo. The method used in this research is normative juridical research, especially Library Law research or secondary data with primary, secondary and tertiary sources of law. The research approaches used include legislative approaches, case studies, conceptual, and analytical methodologies. And the method of collecting such legal materials is carried out by identifying and inventorying positive law, journals and other sources of law. The method used in analyzing the material of grammatical laws and systematic interpretation. And legal construction using analogy construction method and Argumentum a Contrario. The result of this study is a defective deed of sale (AJB) creates uncertainty and reduces the strength of evidence. The Office of the land deed maker (PPAT) who is negligent can be held accountable. Legal protection aims to ensure people's rights through prevention (preventive) and repression (repressive).